The Military ACL - Tennent, David Jackson; Posner, Matthew Adam (The Journal of Knee Surgery, 2019)
Anterior cruciate ligament (ACL) injuries in the U.S. Military Service members have a 10-fold higher incidence than that of the general population due to the physically demanding aspects of military duties. Although some controversy exists on the specific techniques or reconstruction, these injuries are uniformly reconstructed due to the requirements of their occupation and the effect of these injuries on their future careers. As such, understanding the care of the military Service member's ACL may help optimize the care of the physically active injured knee.
Keywords: anterior cruciate ligament; ACL; military